2010
DOI: 10.3758/cabn.10.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Differential neuronal responses to the self and others in the extrastriate body area and the fusiform body area

Abstract: The extrastriate body area (EBA) and the fusiform body area (FBA) are selectively activated by viewing human bodies. However, the role of these functionally defined brain areas in self-other discrimination is still unresolved. Thirty-one females were presented with 16 pictures of their own body and another body in a bikini and with scrambled images while f MRI was performed. Moreover, standardized stimulus material was used in order to localize the EBA and FBA. Region-of-interest analysis showed an enhanced BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 37 publications
5
46
1
Order By: Relevance
“…Indeed, it was described already that the EBA, which typically underlies the N190 amplitudes (Thierry et al, 2006), responds more strongly to movements that are clearly someone else's (David et al, 2009;Myers & Sowden, 2008;Stanley & Miall, 2007; but see Vocks et al, 2010). Because drawing conclusions from the baseline condition of the imitation inhibition task is difficult (see earlier), we can for now not disentangle these two potential interpretations.…”
Section: The Effect Of Action On Perceptionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, it was described already that the EBA, which typically underlies the N190 amplitudes (Thierry et al, 2006), responds more strongly to movements that are clearly someone else's (David et al, 2009;Myers & Sowden, 2008;Stanley & Miall, 2007; but see Vocks et al, 2010). Because drawing conclusions from the baseline condition of the imitation inhibition task is difficult (see earlier), we can for now not disentangle these two potential interpretations.…”
Section: The Effect Of Action On Perceptionmentioning
confidence: 87%
“…As an alternative interpretation, one could assume that the N190 effect could reflect processes of visual (Vocks et al, 2010) or embodied self-other discrimination, which is considered as functionally distinct from high-level, more cognitive self-other distinction (Arzy et al, 2006). Indeed, it was described already that the EBA, which typically underlies the N190 amplitudes (Thierry et al, 2006), responds more strongly to movements that are clearly someone else's (David et al, 2009;Myers & Sowden, 2008;Stanley & Miall, 2007; but see Vocks et al, 2010).…”
Section: The Effect Of Action On Perceptionmentioning
confidence: 99%
“…Another recent study also applying voxel-based morphometry highlighted the role of the extrastriate body area, a region of the occipito-parietal cortex that has been associated with the perception of the own body image, which also had a reduced gray matter volume in anorectic patients (Suchan et al, 2010). Functional magnetic resonance imaging studies employing different paradigms related to the body image have also shown altered activation patterns in this region in patients with AN (Vocks et al, 2010a(Vocks et al, , 2010b(Vocks et al, , 2010c.…”
Section: Objectives Of the Studymentioning
confidence: 95%
“…Also, the left fusiform gyrus and the middle temporal gyrus may reflect a certain degree of body-related avoidance; interventions focused on body image do indeed show an increase in the Extrastriate Body Area (EBA) following successful treatment when patients look at other slim women [53]. We did not replicate the decreased medial prefrontal activation reported by others [18-21]; this is most likely due to the methodological differences related to the stimulus type [54] and to the instruction. Furthermore, as the medial prefrontal cortex is involved in self-referential processing and participants were requested to compare themselves to the women in the pictures, this may have led to an increased activity in the medial prefrontal cortex that counteracted the expected effect.…”
Section: Discussionmentioning
confidence: 72%